KEKHUSUSAN KEWENANGAN KOMISI PEMBERANTASAN KORUPSI DARI KEWENANGAN KEPOLISIAN DAN KEJAKSAAN DENGAN ADANYA UNDANG-UNDANG NOMOR 19 TAHUN 2019 TENTANG PERUBAHAN KEDUA ATAS UNDANG-UNDANG DENGAN NOMOR 30 TAHUN 2002 TENTANG KOMISI PEMBERANTASAN TINDAK PIDANA KORUPSI - Tumbur Ompu Sunggu; Tajuddin (Yuriska: Jurnal Ilmiah Hukum, 2025)
Background: Corruption comes from Latin which means "corruptus" and "corruptio" which literally means rottenness, ugliness, depravity, dishonesty, can be bribed, immoral, and deviation from holiness. Meanwhile, according to KBBI, corruption is the misappropriation or misuse of state money (companies and so on) for personal or other people's benefit. Corruption is also an extraordinary crime. Corruption is said to be an extraordinary crime because corruption is an act of crime that affects the joints of life of a country and society and its nature is very damaging to the country's economy. This act of corruption is an act that is structured, systematically planned and violates human rights. This institution was founded in 2002 by President Megawati Soekarnoputri, with the aim of handling corruption that was deemed unable to be handled by the prosecutor's office and police. Research Metodes: The author uses the normative legal research method (normative juridical). Findings: The Corruption Eradication Commission has special powers that are different from the powers held by the police and prosecutors as referred to in Law No. 2 of 2002, where the KPK's powers are based on Article 6 letter e in conjunction with Article 11 paragraph (1) of Law Number 19 of 2019 concerning the Second Amendment to Law Number 30 of 2002 concerning the Corruption Eradication Commission, which states that the KPK has the authority to conduct investigations and inquiries as well as prosecute corruption casea. Conclusion: With the inclusion of the KPK into the executive branch, the principles of independence based on the concept of state independent agencies and anticorruption agencies are increasingly lost. Several key changes clearly indicate the loss of the KPK's independence. Among others, the placement of the KPK in the executive branch of power, the presence and appointment of the Supervisory Board, the status of KPK employees as ASN, and the status of KPK investigators and investigators. The implication is that the KPK is no longer free from the influence of other powers.